Triglycerides/high density cholesterol ratio and lipid profile in school adolescents from an Andean region of Peru - Ninatanta Ortiz, Juana (2018)
Introduction. Excess weight is a growing phenomenon in the adolescent population, however, studies on the lipid profile in Peruvian adolescents are scarce. Objective. To identify the patterns of triglycerides/HDL cholesterol ratio and lipid profile in schoolchildren without metabolic syndrome in urban areas of an Andean region of Peru. Methods. Secondary analysis database from the study «Frequency of Metabolic Syndrome in residents of an Andean region of Peru». Of 586 students from the original study, 19 were excluded because they had a diagnosis of Metabolic Syndrome. The levels of glucose, total cholesterol, high density cholesterol (HLD), low density cholesterol (LDL) and triglycerides were analyzed. Non-HDL cholesterol was calculated by the difference between total cholesterol and HDL. The triglyceride / HDL cholesterol index (Tg / HDL-C) is the ratio between the serum concentration of triglycerides and HDL cholesterol. Results. We analyzed the lipid profile of 567 adolescents between 11 and 16 years old. The mean of the Tg/HDL-C ratio was 2.9 (standard deviation - SD: 2,35), the median was 2.3 with an interquartile range between 1,62 and 3,51. The Tg/HDL-C ratio ≥3 was associated with higher levels of non-HDL cholesterol, Z-score of BMI and waist circumference. Conclusions. Half of student adolescents in an Andean region of Peru had a Tg/HDL-C index between 1,62 and 3,51. A cut-point ≥3 in the Tg/HDL-C index was associated with a higher concentration of non HDL cholesterol, Z score of BMI, and waist circumference, these last two are indicators of excess weight.